2021
DOI: 10.3389/fmed.2021.649369
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects of Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis With Severe Ocular Complications in Brazil

Abstract: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are acute and potentially fatal inflammatory vesiculobullous reactions that affect the skin and mucous membranes, and which are most often triggered by particular medications and infections. In Brazil, the drugs most frequently associated with TEN and SJS include cold medicine such as dipyrone and NSAIDs, followed by carbamazepine, phenobarbital, penicillin, and allopurinol. Genetic variations have been found to increase the risk of SJS/TEN in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…For example, several previous studies have reported a poor prognosis at only a few years postoperatively, and the prognosis of corneal transplantation in cicatrizing OSD cases is often poor because of a persistent epithelial defect after surgery, infection, the risk of immune rejection, and graft-related problems such as melting or perforation. 19 , 20 In fact, cases with end-stage ocular SJS or TEN reportedly tend to have a worse prognosis after keratoprosthesis caused by postoperative complications, device retention, and poor visual outcome. 21 Cultivated oral mucosal epithelial transplantation (COMET) is one surgical strategy applied for the management of severe OSDs because it successfully reconstructs the cornea for visual improvement and the fornix for symblepharon release and is also effective for the treatment of persistent epithelial defects.…”
Section: Indications For Limbal-rigid Contact Lens Usementioning
confidence: 99%
“…For example, several previous studies have reported a poor prognosis at only a few years postoperatively, and the prognosis of corneal transplantation in cicatrizing OSD cases is often poor because of a persistent epithelial defect after surgery, infection, the risk of immune rejection, and graft-related problems such as melting or perforation. 19 , 20 In fact, cases with end-stage ocular SJS or TEN reportedly tend to have a worse prognosis after keratoprosthesis caused by postoperative complications, device retention, and poor visual outcome. 21 Cultivated oral mucosal epithelial transplantation (COMET) is one surgical strategy applied for the management of severe OSDs because it successfully reconstructs the cornea for visual improvement and the fornix for symblepharon release and is also effective for the treatment of persistent epithelial defects.…”
Section: Indications For Limbal-rigid Contact Lens Usementioning
confidence: 99%
“…These alterations in the microbiome found in patients with ocular SJS, who also had an increased colonisation of pathogenic micro-organisms, may explain the increased risk of severe blinding infections seen in these eyes. Some postulated mechanisms through which the microbiome contributes to the pathogenesis of SJS occur through the compromise of the immunosuppressive environment of the eye and its innate immunity response, upsetting the balance of mucosal immunity and pathogenicity of the surface microbiome and resulting in a chronic and recurrent ocular surface inflammation [10,104,106]. Commensals such as coagulase negative staphylococcus, when identified predominantly from the conjunctiva swabs of SJS patients, seem to be accompanied with severe ocular surface abnormalities such as chronic corneal epitheliopa-thy and a reduced mucin layer of the tear film [35].…”
Section: Ocular Surface Microbiomementioning
confidence: 99%
“…It is essential to consult an ophthalmologist as soon as possible to determine the severity of the ocular involvement and to begin therapy with topical steroids. Patients who undergo particular ophtalmological treatment during the first week of disease are said to have much superior visual outcomes [85]. Ophthalmic steroids and/or intensive eye lubrication may occasionally be needed to treat ocular problems with an inflammatory origin and stop them from progressing to the point where a corneal transplant is ultimately necessary [86].…”
Section: Treatment Of Sequelaementioning
confidence: 99%